Coaching clinic scientific article writing: Increase the awareness of lecturers through a scientific approach - Hardani, H.; Mursiany, Anita; Bimmahariyanto S, Dedent Eka; Ningsih, Kori Puspita; Supinganto, Agus (Journal of Community Service and Empowerment, 2023)
Compiling scientific papers is one of the efforts that can be made by lecturers in developing their professional competence. By writing scientific papers, a lecturer can develop his writing skills, and develop himself to be able to integrate ideas and present them in a structured manner. This activity was carried out to increase lecturer awareness in writing scientific papers and provide education related to writing scientific articles. Preparation for the activity was carried out on August 28 2021 and the core activity was in the form of a coaching clinic for writing scientific articles and was carried out on September 4, 2021. The main target for this activity is young lecturers who have little experience writing articles. The implementation of this service uses coaching clinics, discussions, and assistance. The results of this dedication show an increase in the ability or skills of lecturers and their understanding of writing scientific articles.